The Influence Of Financial Literature, Benefits, Easy And Income On Interest In Using Shopee Paylater (Study On Milenial Generation, Bekasi Regency) - Murti Wijayanti; Heni Rohaeni; Aswiyatul Mukarromah; Tyna Yunita (Peneliti.net, 2022)
This study was used to measure the effect of financial literacy, perceived usefulness, perceived ease of use and income on interest in using Shopeepaylater (a study of the millennial generation Bekasi Regency. This research is quantitative research where the object used is the millennial generation in Bekasi Regency. The number of samples used in this study was 119 respondents. Data collection techniques using questionnaires and data processing and hypothesis testing using SmartPLS 3.0. The results of this study explain that the financial literacy variable has a positive effect on interest in the use, the perceived usefulness has a negative effect on interest use, the perceived ease of use does not effect on interest use and the the income variable does not effect interest in use